A Collaboratively Designed Course: Student Perceptions, Challenges, and a Critical Reflection - Owenz, Meghan (Teaching and Learning Inquiry, 2023)
This paper combines inclusive teaching, cultural humility, and Universal Design for Learning to contextualize the creation and evaluation of human services courses designed collaboratively with students. The collaborative course design was completed in two undergraduate classes with a combined total of 27 student participants. The paper provides reflection of instructor choices in implementing the collaboratively designed courses. Quantitative and qualitative feedback from students is provided and it suggests this activity increased the students’ sense of power in the classroom and enhanced feelings of community and collaboration. The instructor’s critical analysis identifies the benefits of promoting student autonomy, a sense of community, and active learning norms. These benefits were evident, even with the challenges of utilizing significant class time to complete the activity and socializing students to accept the power to make meaningful choices.